Hoorey2 Cupcakes Enterprise / Fatin Sakinah Samsuri... [et al.] - Samsuri, Fatin Sakinah; Md Yusof, Nurlaila; Mohd Bohari, Aznor Aqlili; Abd Jalil, Nur Aisyah (2012)
Hoorey2 Cupcakes Enterprise is a new business venture in the dessert food industry that is expected to run in the early of January 2013. The location of this company will be situated in Sungai Petani, Kedah. It is a partnership agreement established between four well experienced and qualified personnel. Hoorey2 Cupcakes Enterprise is a business that is keen in promoting one of the dessert food products to a bigger audience, particularly in Malaysia. The main product of Hoorey2 Cupcakes Enterprise is cupcakes. There are three flavor that we offer to the customer; Classic Chocolate Mousse, Strawberry Mousse and Vanilla Mousse. We also can design according to the customer wants. Hoorey2 Cupcakes Enterprise aim to attract customer from all ages especially students and families. Our product can be buying from our own shop. Special personal orders are also provided to those who wish to cater with proper delivery services. We also are available via Internet. A special blog is created in promoting and selling our product. Our organization consists of qualified personnel to plan and run the business smoothly to reach the company’s vision, mission and objectives. The appointed General Manager cum Administrative Manager is Fatin Sakinah binti Samsuri, Marketing Manager, NurLaila binti Md Yusof, Operation Manager, Aznor Aqlili binti Mohd Bohari and Financial Manager, Nur Aisyah binti Abd Jalil. Each is focused in their departments and are willing strive for the sake of the company. Hoorey2 Cupcakes Enterprise hopes to meet the demands of every customer and give them a satisfying taste of our product, cupcakes. We hope to be accepted by the food industry and hope to give customers a new perspective towards the dessert food industry in our country. We also hope to introduce cupcakes to a wider audience. Its taste should be known to everyone. For future prospects, we hope to launch our business larger and supply it worldwide.